2016
DOI: 10.1108/mf-07-2015-0187
|View full text |Cite
|
Sign up to set email alerts
|

Dividend initiators, winners during 2008 financial crisis

Abstract: Purpose – The purpose of this paper is to describe and compare the mean response for selected financial variables in three dividend paying groups before and after the financial crisis of 2008. Dividend initiators are expected to be rewarded by investors over traditional dividend paying firms. Design/methodology/approach – Quarterly CRSP data from 2000 to 2012 are used to define dividend paying groups. Highly unbalanced financial data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The second variable confirming this observation is the level of free cash flows, which also turned out to be a statistically significant explanatory variable characterising the period one year before the payment of the dividend took place. Similar results were obtained by Consler and Lepak (2016) who investigated the phenomenon of dividend payments during the financial crisis (though without taking into account the changes over time). The variable explaining the impact on dividend payments in the surveyed companies was GRO: This factor had been previously analyzed in research on the dynamics of dividends conducted by Jinho on a sample of Korean companies (Jeong, 2011) and Yarram and Dollery (2015), who also took into account its variability over time.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The second variable confirming this observation is the level of free cash flows, which also turned out to be a statistically significant explanatory variable characterising the period one year before the payment of the dividend took place. Similar results were obtained by Consler and Lepak (2016) who investigated the phenomenon of dividend payments during the financial crisis (though without taking into account the changes over time). The variable explaining the impact on dividend payments in the surveyed companies was GRO: This factor had been previously analyzed in research on the dynamics of dividends conducted by Jinho on a sample of Korean companies (Jeong, 2011) and Yarram and Dollery (2015), who also took into account its variability over time.…”
Section: Discussionsupporting
confidence: 81%
“…The size of the company matters, as in all countries dividends were paid by the biggest and most profitable firms (Denis & Osobov, 2008). However, this factor is related to profitability, as bigger and more profitable firms are more likely to pay dividends (Consler & Lepak, 2016;DeAngelo et al, 2006). According to Authors, the size of a firm has a significant impact on the relation of retained earnings to total equity.…”
Section: Company Sizementioning
confidence: 99%
“…Nguyen and Tran (2016) came to the same conclusion, that companies in Thailand, Singapore, and the US increased their dividends in the post-crisis period to gain a good reputation, thus supporting the signaling theory. Moreover, Consler and Lepak (2016) also found that investors rewarded the dividend initiator for starting dividends, and all dividend companies grew during the 2008 financial crisis.…”
Section: Dividend Payout and Financial Crisismentioning
confidence: 97%
“…Despite its disastrous effects on the business world, a financial crisis offers a good opportunity to justify the importance of dividend policy. Nguyen and Tran (2016); Consler and Lepak (2016); Abdulkadir, Abdullah, and Wong (2015); Kuo, Philip, and Zhang (2013); He et al (2012); Smits (2012); Mollah (2011);and Reddemann et al (2010), among others, explored the impact of financial distress on firms' ability and willingness to pay dividends. He et al (2012), for instance, discovered that companies' ability to pay during the market crash declined.…”
Section: Dividend Payout and Financial Crisismentioning
confidence: 99%
“…Thus, various reasons have been given to explain the dividend payout options during the financial crisis. Particularly, the signalling theory and catering theory have recently received some attention as explanations for changes in the dividend behaviour of firms in developed markets (Fama & French, 2001;Consler & Lepak, 2016;Chesini & Staniszewska, 2017). Kouser et al (2015) discovered a significant change in the characteristics of dividend payers during their research period on changes in dividend policy following the financial crisis.…”
Section: Introductionmentioning
confidence: 99%